Research on the Quality Improvement of Suburban Cultivated Land - Chen, Weiwei; Li, Yan (International Journal of Agriculture and Food Sciences Research, 2024)
As a transition zone of urban-rural integration, the construction of cultivated land quality in suburban areas is of great significance to ensure food security and promote regional sustainable development. This paper comprehensively analyzes the current situation, problems and influencing factors of suburban cultivated land quality, and proposes corresponding construction strategies. The results show that the construction of cultivated land quality in urban and suburban areas needs to comprehensively consider natural conditions, socio-economic factors and policy orientation, and realize the continuous improvement of cultivated land quality and multi-functional and coordinated development through scientific planning and comprehensive management.